Analisis Kepuasan Nasabah Terhadap Kualitas Layanan PT. Bank Central Asia (Persero) Tbk. - Dewi Alya Febriyani (2021)
The development of the economy in Indonesia is growing so fast that it requires banks to further improve the quality of services and be able to satisfy customers, one of which is PT Bank Central Asia (Persero) Tbk. Customer satisfaction is one of the main keys for a bank in achieving success and growing banking success. Therefore , research was conducted to determine the quality of service to customer satisfaction . The author distributes a questionnaire to 100 customers of Bank BCA with 20 service quality attributes identified from the SERVQUAL (Service quality) indicators, namely (Tengiables, Reability, Responsiveness, Assurance, Empathy) which are used to measure the quality of Bank BCA services and use the Importance Performance Analysis (IPA) method. to determine the level of importance and performance of service quality attributes.